2014
DOI: 10.1371/journal.pone.0100789
|View full text |Cite
|
Sign up to set email alerts
|

Association between Thrombophilia Gene Polymorphisms and Preeclampsia: A Meta-Analysis

Abstract: ObjectiveTo estimate the relationship between the risk of preeclampsia and two thrombophilia gene single-nucleotide polymorphisms (SNPs), the factor V G1691A SNP and the prothrombin G20210A SNP.Date SourcesA systematic search of the English-language literature up to November 2012 was performed using Medline and EMBASE. Search terms included “preeclampsia,” “thrombophilia,” “factor V Leiden,” “prothrombin gene 20210,” and their combinations.Result(s)Thirty-seven studies with 5048 preeclampsia patients and 6796 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 52 publications
1
31
0
3
Order By: Relevance
“…Summarizing the data presented above, we can note the following patterns: The obtained data are consistent with the results of previously published meta-analyses and clinical recommendations [17][18][19]21]. Nevertheless, despite an associative, statistically significant relation between FVL 1691 GA and the risk of VTEC development and pregnancy complications, up to now there are no international recommendations for the prevention of pregnancy complications in FVL 1691 GA patients.…”
Section: Clinical Manifestation Of Fvl 1691 Ga In Pregnancy Complicatsupporting
confidence: 88%
See 1 more Smart Citation
“…Summarizing the data presented above, we can note the following patterns: The obtained data are consistent with the results of previously published meta-analyses and clinical recommendations [17][18][19]21]. Nevertheless, despite an associative, statistically significant relation between FVL 1691 GA and the risk of VTEC development and pregnancy complications, up to now there are no international recommendations for the prevention of pregnancy complications in FVL 1691 GA patients.…”
Section: Clinical Manifestation Of Fvl 1691 Ga In Pregnancy Complicatsupporting
confidence: 88%
“…The world community developed protocols and algorithms for the prevention of VTEC, depending on the degree of occurrence risk of the factor V Leiden mutation. However, the clinical manifestations of factor V Leiden are heterogeneous and can be not only in the form of thromboembolic events but also determine the risk of developing gestational complications, including the great obstetrical syndrome [15][16][17]. Modern ideas about the relation between FVL 1691 GA carriage and the risk of developing gestational complications are highly contradictory, the available studies in this direction are inadequate and ethnically heterogeneous and often contradict with each other [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…We did not find any association of F5:c.1601G > A with preeclampsia in our cohort. Though the F5 is one of the thrombophilic genes and its variants may have a key role in the development of the preeclampsia; however, the association of F5:c.1601G > A with thrombophilia and preeclampsia has remained controversial among studies; conducted on patients with different ethnic groups [31]. It has been found that F5:c.1601G > A is common in Northern India and predisposes women to preeclampsia [20]; which is contradictory to our results, though patients may have common ethnic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…The ambiguity of reliable data on the etiology and pathogenesis of these placenta-mediated conditions does not allow to develop a universal complex of measures for their effective prevention in the population. One of the proven risk factors for disrupting placenta formation is the genetic thrombophilias, in particular Factor V Leiden mutation [1,3,4]. This is a point mutation of the proaccelerin factor gene, accompanied by the replacement of the guanine nucleotide by adenine at position 1691 (FVLG1691A), which leads to the replacement of the amino acid Arginine (Arg =R) by the amino acid Glutamine (Gln =Q) at position 506 (FV R506Q) in the protein chain, which is the product of this gene.…”
Section: Introductionmentioning
confidence: 99%